HOSPITALITY INDUSTRY CAREERS: ANALYSIS ON STUDENTS INTEREST BASED ON DIFFERENT LOCATION OF UPBRINGING AND SECONDARY SCHOOL BACKGROUND - R.A FRASER (ASEAN Journal on Hospitality and Tourism, 2008)
One of the many challenges facing the Malaysian hospitality industry is the attraction and retention of young people in highly competitive employment market. Beside other issues, the low numbers and poor transfer rate of graduates into the industry were found to be the most critical problems in the country. One of the causes of poor transition of hospitality students into careers in the industry is that new student have an unrealistic image ofworking life in the industry. This might stem from a number offactors influencing students' interest and attitudes towards hospitality careers. While a number of previous studies have focused on the students ' attitudes and perception of careers in the hospitality industry in general, none investigated pre-tertiary education influences on career attitudes. This study investigated the relationships between geographical location of upbringing, type of secondary schools attended and attitudes and motivation of Malaysian hospitality students towards hospitality career.A sample of students (yearl , 2 and 3) of diploma Culinary Arts, Hotel Management and Food Service Management from Faculty of Hotel and Tourism Management, MARA University of Technology , Malaysia (Shah Alam, Dungun and Penang campuses) were used in this study. A total 469 useable questionnaire were collected comprises of 173 of year -one, 161 of year- two and 135 of year-three. Despite no sustained impact on the perceptions or expectations of hospitality students through the programme, there are some distinct differences at the start of their tertiary programme between students from different types of secondary schooling and areas of upbringing. Students from rural areas identify themselves of having unclear idea and less knowledgeable about the programme and industry at the time of making their career choice as compared to those from towns and cities. Similarly, students from normal secondary schools backgrounds also classify themselves as less informed, having more unrealistic perceptions and views about the industry than those from vocational schools. It is recommended that career guidance and orientation should be made more effective especially at the normal secondary schools to ensure students are informed realistically and sufficiently about careers and working conditions in the hospitality industry. Developing more realistic and lower expectations about working in the industry will allow young people to choose to study in a hospitality programme based on a considered career decision rather than by a chance matching of personal needs with what the industry has to offer. In addition, there is a need to educate parents, as well as young people, in the rural areas about these career options and vocational education should be more highly promoted to the rural youth.